Funciones como asistente de: Tesorería - Contable en la empresa Ferretería Industrial KOU S.A.C. - Jordán Castro, Sandra Natalia (2019)
This report is based on my work experience in the years 2010 to 2013 During the time I have worked in the company it was necessary to apply all the knowledge I was given during my studies at the National University of Trujillo and thus update the information received at that university time, which describes my obligations which helped me to climb little too little and to understand more the necessity to be updated in this race since its branches are diverse and infinite to learn. Each step taken in the company has served me a lot since I have been able to contrast the teachings of the University, remember the extraordinary teachings of our best professors that this great house of studies has. My start was as Accounting assistant and then I assumed the responsibility of taking the Treasury in which at the beginning it was chaotic, but little by little, updating the accounting system, defining and separating tasks that corresponded only to the Treasury area, it was possible to affirm my position in the company. Thus, the following experience report in the professional field is based on all the experience acquired in Kou S.A.C. which has been the beginning of my development as a professional and I have been able to see how it develops Accounting with the information it processes and presents in a timely manner to management and then start with the decision-making process in its growth.